1981
DOI: 10.1038/bjc.1981.204
|View full text |Cite
|
Sign up to set email alerts
|

Mammary-tumour incidence in Sprague-Dawley rats treated with 7,12-dimethylbenz(a)anthracene: Effect of pregnancy and lack of effect of unilateral lactation

Abstract: Summary.-Mammary teat removal (thelectomy) was performed unilaterally in female Sprague-Dawley rats at 35 days of age. They were given 7,12-dimethylbenz-(a)anthracene (DMBA) when aged either 55 days or 79 days. One third were unmated; one third were mated one week and one third mated more than 3 weeks after DMBA administration. Animals were killed when tumour-positive or after one year, when mammary lesions had developed in 99 o of rats. The mean latent period for adenocarcinomas was 18-9 + 2-0 weeks. Benign m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The comparison of the effect of hCG treatment with that of pregnancy is straightforward with results reported by Grubbs et al (1983aGrubbs et al ( , 1986 and Moore et al (1981), who found a protective effect when pregnancy was initiated soon after carcinogen administration. Dao et al (1960) also reported complete inhibition of tumorigenesis when pregnancy was initiated simultaneously with carcinogen administration, and reduced overall tumour incidence when pregnancy was initiated at a later date, although these authors report decreased latency period and greater short term tumour incidence.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…The comparison of the effect of hCG treatment with that of pregnancy is straightforward with results reported by Grubbs et al (1983aGrubbs et al ( , 1986 and Moore et al (1981), who found a protective effect when pregnancy was initiated soon after carcinogen administration. Dao et al (1960) also reported complete inhibition of tumorigenesis when pregnancy was initiated simultaneously with carcinogen administration, and reduced overall tumour incidence when pregnancy was initiated at a later date, although these authors report decreased latency period and greater short term tumour incidence.…”
Section: Discussionmentioning
confidence: 52%
“…mammary gland from neoplastic transformation (Dao et al, 1960;Russo et al, 1980Russo et al, , 1987a, whereas pregnancy initiated after carcinogen administration has been reported to shorten the latency period, to accelerate the growth of mammary cancer and to increase the number of active centres (Huggins et al, 1962). Dao et al (1960) also reported shortened latency period in tumour development during pregnancy and increased short term tumour incidence, but decreased overall tumorigenic response, whereas Moore et al (1981) and Grubbs et al (1986) found pregnancy to be protective. It has been shown that the protective effect of pregnancy prior to carcinogen administration is due to induction of differentiation of the mammary gland (Russo et al, 1978(Russo et al, , 1980, however, the exact mechanism of action of each specific hormone prior to or after carcinogen administration is not known.…”
mentioning
confidence: 98%
See 3 more Smart Citations